New Latrunculiidae (Demospongiae, Poecilosclerida) from the Agulhas ecoregion of temperate southern Africa - Samaai, Toufiek; Kelly, Michelle; Ngwakum, Benedicta; Payne, Robyn; Teske, Peter R.; Janson, Liesl; Kerwath, Sven; Parker, Denham; Gibbons, Mark J. (Zootaxa, 2020)
Sixteen species of Latrunculiidae Topsent, 1922, belonging to the genera Latrunculia du Bocage, 1869, Strongylodesma Lévi, 1969, Cyclacanthia Samaai & Kelly, 2004, Samaai & Kelly, 2002, are currently known from the temperate waters of South Africa. Extensive new sponge collections from the Amathole region of South Africa revealed the existence of three new species of Tsitsikamma, T. amatholensis sp. nov., T. madiba sp. nov., and T. beukesi sp. nov., and a new species of the endemic South African genus Cyclacanthia, C. rethahofmeyri sp. nov. With the recent addition of two new species of Tsitsikamma from Algoa Bay and Tsitsikamma National Park (T. michaeli Parker-Nance, 2019; T. nguni Parker-Nance, 2019) the total number of known South African Latrunculiidae is now 20 species in four genera. Here we propose two new subgenera of Tsitsikamma, Tsitsikamma Samaai & Kelly, 2002 and Clavicaulis subgen. nov., based on the morphological groups “favus” and “pedunculata” hypothesized by Parker-Nance et al. (2019). Species in the nominotypical subgenus Tsitsikamma, containing the type species, are thick encrusting to hemispherical with a rigid honeycombed choanosome, while species in the new subgenus Clavicaulis subgen. nov. have a purse or sac-like morphology with little choanosomal structure. Despite the obvious species-level differences in morphology, multivariate analysis based on spicule measurements (anisostyle length, discorhabd length, shaft and whorl length) was not able to distinguish between the proposed Tsitsikamma species, but separated known species T. favus Samaai & Kelly, 2002, T. pedunculata Samaai & Kelly, 2003, and T. scurra Samaai & Kelly, 2003, from each other. Similarly, DNA barcoding of the mitochondrial COI  and the nuclear ITS of Tsitsikamma specimens failed to clearly differentiate between species, but was able to differentiate sister taxon relationships within the Latrunculiidae.